Kepemimpinan Kristen di Era Bonus Demografi Pasca Sensus Penduduk Indonesia Tahun 2020 - David Eko Setiawan (IAKN TORAJA, 2021)
Abstract: The results of the 2020 population census show that Indonesia is still in the era of demographic bonuses. This phenomenon can be a boon and a disaster if not appropriately addressed. Christian leadership should see this as a challenge and opportunity for the development of the present and future church. This article aims to explain Christian Leadership in the era of demographic bonuses after the 2020 Indonesian population census. While the research problem in this study is how Christian leadership in the era of demographic bonuses post-census population of Indonesia in 2020? The method used in this study is the library method. The result of this study is Christian leadership in the era of demographic bonuses post-census population of Indonesia in 2020 must be responsive to the changing times, must think about the outreach model of the younger generation more relevant and contextual, should present a holistic service model. Keywords: Christian Leadership, Demographic Bonuses, Population Census Abstrak: Hasil sensus penduduk tahun 2020 menunjukkan bahwa Indonesia masih berada pada era bonus demografi. Fenomena ini dapat menjadi anugerah dan petaka jika tidak disikapi secara tepat. Kepemimpinan Kristen seharusnya memandang hal tersebut sebagai tantangan dan peluang bagi pengembangan gereja masa kini dan masa depan. Artikel ini bertujuan menjelaskan Kepemimpinan Kristen di era bonus demografi pasca sensus penduduk Indonesia tahun 2020. Sedangkan reseach problem dalam penelitian ini adalah bagaimanakah Kepemimpinan Kristen di era bonus demografi pasca sensus penduduk Indonesia tahun 2020? Metode yang digunakan dalam penelitian ini adalah metode kepustakaan. Hasil dari penelitian ini adalah Kepemimpinan Kristen di era bonus demografi pasca sensus penduduk Indonesia tahun 2020 wajib tanggap terhadap perubahan zaman, wajib memikirkan model penjangkauan generasi muda yang lebih relevan dan kontekstual, seyogyanya menghadirkan model pelayanan yang holistik. Kata Kunci: Kepemimpinan Kristen, Bonus Demografi, Sensus Penduduk